مستوى الاستغراق الوظيفي لدى أساتذة كلية العلوم الاجتماعية في ظل التعليم عن بعد - بن سعدة محمد صفي الدين; طالب يوسف عبد الفتاح; عمومن رمضان (My University, 2021)
This study aimed to know the level of job absorption among the professors of the Faculty of Social Sciences at the University of Laghouat in light of distance education, and it was conducted based on the following questions: What is the level of job absorption among the professors of the Faculty of Social Sciences in light of distance education? 2. Are there differences in the job involvement of the study sample members due to the variable of occupational rank? 3.Are there differences in the job engagement of the study sample members due to a change in seniority? 4. Are there differences in the spectral ethnicity of the study sample members exposed to the gender variable? In this study, the descriptive approach was relied, and the questionnaire tool was used, where the job engagement scale was applied to a sample of (55) professors of the Faculty of Social Sciences, and the statistical treatment was carried out by the Statistical Packages Program for Social Sciences. (SPSS), the study yielded the following results: 1- The professors of the Faculty of Social Sciences have a low level of job engagement under the online education. 2. There are no differences in the level of job absorption among the sample members due to the variable occupational rank 3. There are no differences in the level of job absorption among the sample members due to the variable of seniority, 4, there are no differences in the level of job absorption among the study sample members due to the gender variable. In light of these results, we say that the results of the study are limited to its spatial, temporal, human and instrumental limits, and it cannot be generalized to all professors job engagement , professors of the Faculty of Social Sciences, distance education.